The Effect of Acceptance of People Friends on Students' Learning Motivation in Class XI IPA SMA Negeri I Bonjol Regency Pasaman - Ayu, Nuzul Putri (Lembaga Riset Mutiara Akbar, 2022)
The problem studied based on the phenomenon that researchers found in the field is the behavior of peer acceptance of the learning motivation of students in the school environment at this time is not in accordance with what it should be. Students also play an important role in the acceptance of peers, especially in motivation. So the researcher raised the research problem about how the influence of peer acceptance on the learning motivation of students at SMA Negeri 1 Bonjol, Pasaman Regency. This study aims to describe the acceptance of students' peers, students' learning motivation, the influence of peer acceptance on students' learning motivation. The type of research used is simple linear regression analysis. The population in this study were students of SMA Negeri 1 Bonjol. This sample was taken using a random sampling technique. From the calculation results obtained a sample of 105 people. The instrument used in this research is a questionnaire. To analyze the data, the Pearson Product Moment formula was used in order to see the relationship between the influence of peer acceptance on the learning motivation of students at SMA Negeri 1 Bonjol, Pasaman Regency